Outcome analysis of cubital tunnel decompression. Issue 3 (August 2015) - Jariwala, A; Bansal, N; Nicol, GM; Shelton, J; Wigderowitz, CA
Background: Cubital tunnel decompression is a commonly undertaken upper limb procedure. Most studies compare the different techniques of decompression; however, only a few have specifically investigated the outcome of ulnar nerve decompression. Aim: The aim of this study was to investigate the outcome of ulnar nerve decompression following cubital tunnel syndrome. Methods and results: A total of 174 ulnar nerve decompression cases were identified from the upper limb surgery database with complete data available for 136 cases. Simple decompression was performed in 110 (80.88%) cases, and in 26 (19.12%), anterior subcutaneous transposition was also supplemented. These operations were performed at three different hospitals by surgeons of different levels of experience. The most common cause of cubital tunnel syndrome was idiopathic. The outcome was satisfactory in 86% of cases. No obvious association was demonstrated between the outcome of surgery and duration of symptoms, presence of co-morbidities or the type of surgery performed. Conclusion: This is the largest outcome analysis of the results of ulnar nerve decompression at the elbow. Good results following nerve decompression were attained in 86% of cases without any significant effect of duration of symptoms or co-morbidities on the outcome of surgery. It is hoped that the findings of the current study will help general practitioners, junior doctors and surgeons in their management and pre-operative consultation with patients having cubital tunnel syndrome.